Assessment of Availability and Quality of Emergency Obstetric and Newborn Care Service in Southwestern Oromia, Ethiopia, 2017 - Dejene Edosa (Advances in Public Health)
Background. Emergency obstetrics and newborn care (EmONC) is an important lifesaving function which can avert the death of women facing obstetrics-related complications. It is a cost-effective, significant intervention to decrease maternal and neonatal morbidity and mortality in poor resource settings, including Ethiopia. Objective. The aim of this study was to assess the availability and quality of the EmONC services in southwestern Oromia, Ethiopia, in 2017. Methods. An institutional-based cross-sectional study was implemented from April to May 2017. Data were collected using checklists and questionnaires developed from different studies. Data were analyzed using EPI-info and exported to SPSS version 20 for further analysis. Each descriptive statistic was summarized using frequency, percentage, and tables for categorical variables. Results. Despite the fact that the overall coverage of fully functioning basic emergency obstetric and newborn care (BEmONC) facilities was greater than 5 per 500,000 people, nearly one-fourth (25.64%) provided less than expected signal functions, indicating that these facilities were nonfunctional. There were only 0.24 comprehensive emergency obstetric and newborn care (CEmONC) facilities per 500,000 people. The result of this study also revealed that the quality of EmONC facilities in all health-care settings was poor. Conclusion and Recommendation. There were gaps in performance signal functions as well as the availability and quality of EmONC in the study area. Availability and quality of EmONC necessitate improvements through enhancing health-care providers’ skills by training and mentoring as well as enabling facilities accessible for utilization of EmONC. Further research is needed to identify factors that could be barriers to the performance quality and coverage of EmONC services.